RAMAYANA: TIMELESS LESSONS FOR MODERN SOCIETY - Anjaria, Dhairyavi (ShodhKosh: Journal of Visual and Performing Arts, 2022)
The Ramayana has long been a cornerstone in shaping the moral, cultural, and social fabric of Indian society. Its profound influence extends beyond a mere tale of heroism and devotion; it serves as a blueprint for righteous living, emphasizing values such as integrity, duty, loyalty, and compassion. The epic fulfills a dual purpose, offering entertainment while imparting life lessons that have been passed down through generations. These teachings have profoundly shaped the values and ideals of Indian society, weaving them into its collective consciousness. In the modern era, technological advancements are often criticized for alienating individuals from their cultural roots and eroding traditional values. However, the Ramayana continues to hold relevance, even amidst rapid societal changes. This paper seeks to explore the enduring presence of Ramayana’s ideals in contemporary society and the ways in which these values have adapted to the challenges of modern life. Additionally, it examines the evolving portrayal of the Ramayana through various mediums, from oral storytelling and theatrical performances like Ram Leela to cinematic and televised renditions. By delving into its continued influence on art, culture, and social structures, this study aims to highlight how the Ramayana reinstalls’ lost values, reminding society of its rich ethical and cultural heritage in an ever-changing world.